PENINGKATAN ANGKA PERCERAIAN SAAT COVID-19 DI PENGADILAN AGAMA JAKARTA SELATAN - Sunarto, Sunarto; Fadilah, Tubagus (Asosiasi Dosen PTKIS Indonesia, 2024)
Divorce is an emergency door that can only be passed in urgent circumstances. Therefore, Islam provides its final solution to married couples who experience disharmony in building their households, namely by divorce (talaq). The research on